A huge intra-abdominal hematoma with an unusual etiology - Chen, Yen-Cheng; Tsai, Hsiang-Lin; Yeh, Yung-Sung; Huang, Ching-Wen; Chen, I-Shu; Wang, Jaw-Yuan (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Chen YC, Tsai HL, Yeh YS, Huang CW, Chen IS, Wang JY. A huge intra-abdominal hematoma with an unusual etiology. Turk J Gastroenterol 2019; 30(6): 565-8